Multiple topics evolution model based on similarity of interference - Yefei CHEN; Xuejun ZHANG; Weidong HUANG (Dianxin kexue)
The current researches of evolution model mainly focus on the spread of the individual topics,rarely considering the influential factors between multiple topics.A new topic evolution model was proposed by considering the interference among topics based on SIR model,which characterized by the influence of the similarity of the topic on the probability of propagation.The experimental results show that within the critical value,the similarity degree of positive and negative trends enhance or hinder the process of topic evolution,and the degree of action varies with the degree of interference nodes,which is expressed as evolutionary consistency under positive similarity and the evolutionary separability under negative similarity.When the critical value is exceeded,the effect of strengthening or hindering tends to saturation.